2023
DOI: 10.1186/s12886-023-02874-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep-wake schedules and myopia among Chinese school-aged children and adolescents: a cross-sectional study

Abstract: Background This study aimed to investigate the relationship between sleep-wake schedules and self-reported myopia in the pediatric population. Methods In this cross-sectional study in 2019, school-aged children and adolescents in the Baoan District of Shenzhen City were sampled using a stratified cluster sampling approach. Sleep-wake schedules of children were determined by a self-administered questionnaire. The age that participants first reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Sleep is under circadian and homoeostatic control and may also contribute to ocular growth and emmetropization [ 250 ]. Myopic children have recently been reported to exhibit delays in sleep onset and wake-up time, which aligns with delays in DLMO [ 248 ], in addition to reduced sleep quality [ 248 , 251 ] compared to emmetropes. Furthermore, it has been postulated that lack of sleep or later bedtime could lead to additional near work, and thus higher risk for myopia [ 252 ].…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…Sleep is under circadian and homoeostatic control and may also contribute to ocular growth and emmetropization [ 250 ]. Myopic children have recently been reported to exhibit delays in sleep onset and wake-up time, which aligns with delays in DLMO [ 248 ], in addition to reduced sleep quality [ 248 , 251 ] compared to emmetropes. Furthermore, it has been postulated that lack of sleep or later bedtime could lead to additional near work, and thus higher risk for myopia [ 252 ].…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…Research supported that su cient sleep served as a protective factor against myopia [51]. The bene cial effect of sleep on myopia might be attributed to the relief or rest it provides to the ciliary muscle, thereby helping to prevent or alleviate myopic progression [52].…”
Section: The Epidemiological Characteristics Of Myopia Prevalence Amo...mentioning
confidence: 99%
“…Various sleep parameters, particularly bedtime, sleep quality, and duration, have been investigated in myopia but, thus far, have yielded mixed results. Several studies have found that children with myopia sleep later than children without myopia [16][17][18][19] , while some have found no association [20][21][22][23] . Myopia has been associated with lower sleep quality in some studies 16,24 , while no associations have been found in others 25 .…”
Section: Introductionmentioning
confidence: 99%